Creating an Encouraging Learning Environment for Multicultural Groups in Linguistic Integration Courses - Zagrebina, Anna (The Canadian Journal for the Study of Adult Education / La revue canadienne pour l’étude de l’éducation des adultes)

(untitled) (Canadian Association for the Study of Adult Education / L’Association canadienne pour l’étude de l’éducation des adultes, 2025)
Teaching multicultural groups of adult learners has become a widespread practice in immigrant-receiving countries. However, not enough was said about the practical strategies for managing these groups, where all the participants may have different cultural values and, consequently, very different ideas about the educational process and the roles of a student and an instructor in it. This article, therefore, presents an effective strategy for creating a supportive learning environment while working with adult immigrant learners from different countries. This approach was developed and tested in practice over years of working with such groups of students in linguistic integration courses in Quebec and can be summarized as follows: treat students on a human level and avoid emphasizing their cultural identity in the educational process.